ANALISIS ETNOMATEMATIKA JEJAHITAN BALI DALAM PEMBELAJARAN BANGUN DATAR - Puspadewi, Kadek Rahayu; Wulandari, I Gusti Ayu Putu Arya (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
Mejejahitan is one of the cultural arts in Bali. Mejejahitan is an activity to get shapes from pieces of leaves. The results of this activity are known as jejahitan. This research is a qualitative research. The purpose of this research is to analyze the etnomathematics that exist on the Jejahitan Bali. The subjects of this study were four housewives from Ubud village as many as four people.Data in this study were obtained through interviews and observations. The data obtained are then analyzed with three steps, namely reduction, presentation, and conclusions. Mathematical elements found in the Jejahitan Bali include square, rectangle, triangle, isosceles trapezoid, and circle. This plane shapes can be used in teaching planimetry especially the properties of the plane, the area and perimeter, line of symmetry and rotational symmetry of plane shapes.